Clothing, Caste, and the Politics of Dignity: Re-reading the Upper Cloth Revolt through the Radical Thought of B. R. Ambedkar and E. V. Ramasamy (Periyar) - Anji A. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
The Upper Cloth Revolt (commonly known as the Thol Seelai Porattam) in the princely state of Travancore during the nineteenth century stands as a powerful yet under-theorized episode in the history of anti-caste and gender resistance in South Asia. This paper argues that the revolt must be understood not as a localized dispute over dress codes but as a radical assertion of dignity, bodily autonomy, and social equality by marginalized women, particularly from the Nadar community. By situating this movement within the intellectual frameworks of B. R. Ambedkar and E. V. Ramasamy, the paper demonstrates how the politics of clothing functioned as an instrument of caste domination and how resistance to it anticipated later critiques of Brahminical patriarchy. Drawing on historical accounts and critical theory, the study foregrounds the revolt as a foundational moment in the genealogy of social justice movements in India.